Fear of Fat, Processes of Change, and Weight-Related Behaviors in Mexican and Spanish Adolescents - María Marentes-Castillo; Isabel Castillo; Inés Tomás; Olivia González-Acevedo; Octavio Álvarez (MDPI AG, 2024)
Background: Fear of fat is a relevant variable in initiating weight regulation behaviors in adolescents. However, little is known about the experiential and behavioral change processes that mediate the choice between healthy and unhealthy weight regulation behaviors in this population. Method: The general objective was to examine the predictive role of fear of fat on weight-related behaviors (healthy and unhealthy weight control behaviors) through the mediation of experiential and behavioral change processes (consciousness raising, counterconditioning, helping relationships, reinforcement management, self-liberation, self-reevaluation, stimulus control, substance use) in 838 adolescents aged 15-19 years from Mexico and Spain using parallel mediation analysis. Additionally, the study examined the correlations between the variables with regard to gender and country, as well as the differences in the use of processes of change across stages of change through the use of a multivariate analysis of variance. The Spanish version of the Fear of Fat, Stages of Change, Processes of Change, and Weight-Related Behaviors scales were used. Results: The mediation analysis showed that fear of fat predicted healthy weight control behaviors through consciousness raising, self-liberation, and stimulus control. On the other hand, fear of fat predicted unhealthy weight control behaviors through counterconditioning, stimulus control, and the use of weight loss substances. Intervening to reduce fear of fat may be a way to modify the processes of change used by adolescents to regulate their weight. Conclusions: The results of this study indicate that adolescents may initiate weight control behaviors as a result of fear of fat. This process is mediated by experiential and behavioral processes that influence weight regulation.